Jing-Yin-Gu-Biao formula protects mice from postinfluenza Staphylococcus aureus infection by ameliorating acute lung injury and improving hypercoagulable state via inhibiting NETosis - Lei, Biao; Mu, Jingwen; Xu, Guihua; Yang, Xiaodong; Huang, Wenbo; Hu, Liang; Liu, Dan; Cheng, Ting; Ma, Yuhe; Xu, Lirong; Liang, Qiankun; Lin, Yuan; et al. (Frontiers in Immunology, 2025)
BackgroundJing-Yin-Gu-Biao formula (JYGBF) is a Chinese medicine derived from Yupingfeng power, Huoxiangzhengqi powder and Yinqiao powder, and has been widely used to treat acute respiratory infections. This study aims to observe the effects of JYGBF against postinfluenza Staphylococcus aureus (S. aureus) infection.Purpose and study designA mouse model of secondary S. aureus infection following PR8 infection was established to evaluate the protective effects of JYGBF against postinfluenza Staphylococcus aureus (S. aureus) infection and related mechanisms were validated in vivo and in vitro.ResultsThe administration of JYGBF significantly ameliorated acute lung injury (ALI) and inhibited overactivated inflammatory response (MIP-2, IL-6, etc.) in mice with postinfluenza S. aureus infection. Single cell RNA-sequencing (scRNA-seq) data indicated that neutrophils had the highest cytokine score in lungs and JYGBF inhibited neutrophil chemotaxis, reactive oxygen species (ROS) biosynthesis and ERK1/2 cascades in neutrophils. Meanwhile, JYGBF inhibited the formation of neutrophil extracellular traps (NETs) in lungs, which is characterized by the production of ROS, peptidyl arginine deiminase 4 (PAD4), citrullinated histone H3 (CitH3), myeloperoxidase (MPO), neutrophil elastase (NE), S100A8/A9 and MPO-CitH3 colocalization. Moreover, JYGBF decreased platelet counts and the expression of its activated markers (CD62P and αIIbβ3) accompanied by the drop of fibrinogen (FIB) and fibrin degradation product (FDP), accounting for alleviating hypercoagulable state. JYGBF inhibited ERK1/2 phosphorylation in neutrophils and in lungs of infected mice. Acacetin, a critical compound from JYGBF, inhibited NET formation via downregulating ERK/ROS axis.ConclusionsThese results indicated that JYGBF inhibited NET formation and overactivated inflammatory response by suppressing ERK/ROS axis in neutrophils, thereby mitigating ALI and improving the hypercoagulable state during postinfluenza S. aureus infection. JYGBF could be considered a potent therapeutic agent for the prevention and treatment of postinfluenza bacterial infection.